INTERPRETING BALINESE MYTHOLOGY-THEMED CHARACTER DESIGN SIGNIFICATION AS A VIRTUAL ENTITY IN ANIMATION - Yusa, I Made Marthana; Ardhana, I Ketut; Darma Putra, I Nyoman; Pujaastawa, Ida Bagus Gde (E-Journal of Cultural Studies, 2023)
This article explores the significance of Balinese mythology-themed character design in animation as virtual entities, providing an in-depth analysis of their cultural signification and cultural implications, and their role in promoting social commentary and cultural preservation. Through the use of case studies, literature reviews and survey, the articles examines how various Balinese mythological figures including ( Hanoman, Garuda , Barong , and Rangda ) are portrayed in popular animated works and what cultural meanings are conveyed through their design choices. The article analysis reveals that Balinese mythology-themed character design in animation can reflect Bali cultural values, promote social commentary, beliefs, and traditions, serving as a means of preserving Balinese cultural heritage. Furthermore, the results demonstrate the importance of considering the cultural context in which mythology is presented in animation, as it can shape the interpretation of these virtual entities.   Keywords: Balinese mythology-themed, character design, signification, virtual entity